Analyzing the Practice of Critical Thinking Skills for Islamic Education Students in the International Campus - Pandang Margatama; Tahraoui Ramdane; Muhammad Wildan Shohib (Universitas Muhammadiyah Malang, 2023)
Critical thinking is one of the most important goals of any educational system. Previous research has indicated that Malaysian educational institutions are still unable to meet the goals of instructional pedagogy in the classroom, particularly in terms of improving critical thinking abilities. The purpose of this study is to examine the practice of critical thinking skills among undergraduate students from the perspective of faculty members. This study is qualitative in nature since it focuses on individuals’ experiences and impressions of a specific programs from their own viewpoints. Data was gathered through interviews with faculty members who teach Islamic Education undergraduate students at the Kulliyyah of Education (KOED), International Islamic University Malaysia (IIUM). The findings of the study revealed that practicing critical thinking abilities improved the students’ learning experiences. According to the informants’ response, a critical thinking skill is the student's ability to gather knowledge and explain his or her thoughts in order to solve difficulties. Similarly, students may exercise critical thinking abilities by developing higher-order thinking skills, problem-solving skills, reflection skills, and synthesis skills. Moreover, the study recommends further investigations on the practice of critical thinking skills not only for undergraduate students but also for other postgraduate students, particularly at the Kulliyyah of Education (KOED), IIUM. It also suggests that management educational institutions offer intensive programs to help students strengthen their critical thinking abilities.